Method for improving rotational fatigue performance of additive manufacturing aluminum-based composite material

By ball milling and mixing AlMnMgZrHf alloy powder and TiB2 powder for additive manufacturing and heat treatment, a specific microstructure is formed, which solves the problem of insufficient rotation fatigue performance of aluminum-based composite materials and significantly improves the fatigue strength and durability of the material.

CN119410943APending Publication Date: 2025-02-11NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411601954.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The rotational fatigue performance of existing aluminum-based composite materials is not sufficient to meet the needs of the industry, especially in the long-term use, fatigue cracks are easily generated, resulting in component failure.

Method used

Additive manufacturing is carried out by ball milling and mixing the AlMnMgZrHf alloy powder and TiB2 powder, followed by heat treatment, and formed in the fine grain region at the boundary of the melt pool and the coarse grain region inside the melt pool. There is a microstructure of the Al3 (Ti, Zr, Hf) phase.

Benefits of technology

The rotation fatigue performance of aluminum-based composite materials is significantly improved, so that the rotation fatigue load of the aluminum-based composite materials is greater than 175MPa while satisfying 1×107 cycles, which improves the fatigue strength and durability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410943A_ABST
    Figure CN119410943A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the rotational fatigue performance of an additive manufacturing aluminum-based composite material. The method comprises the following steps that firstly, AlMnMgZrHf alloy powder is prepared; secondly, the alloy powder and the TiB2 powder are subjected to ball milling, and composite material powder is obtained; 3, the composite material powder is subjected to additive manufacturing, and a sedimentary sample is obtained; and fourthly, the sedimentary-state sample is subjected to heat treatment, and the heat-treatment-state additive manufacturing aluminum-based composite material sample is obtained. Aluminum alloy powder and TiB2 powder are subjected to ball milling, then additive manufacturing is carried out, then heat treatment is carried out, and the obtained microstructure is that an Al6Mn phase is distributed along the grain boundary, Al3 (Ti, Zr and Hf) phases exist in a molten pool boundary fine grain area and a molten pool internal coarse grain area, and due to the precipitation strengthening effect of a large number of the two phases in the heat treatment process, the thermal conductivity of the molten pool is improved. And the rotary fatigue load of the heat-treated additive manufacturing aluminum matrix composite sample is greater than 175 MPa under the condition that the cycle index is 1 * 107.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of improving the rotational fatigue performance of additively manufactured aluminum-based composite materials, and specifically relates to a method for improving the rotational fatigue performance of additively manufactured aluminum-based composite materials. Background Art

[0002] Laser powder bed fusion (L-PBF) is also called selective laser melting (SLM) technology. Its manufacturing principle is to reduce the dimensionality of complex three-dimensional structures layer by layer, and form complex three-dimensional parts by layer-by-layer powder laying, melting and solidification. L-PBF is one of the most important and most promising metal additive manufacturing (AM) technologies. High-energy laser beams act as movable heat sources with extremely fast heating and cooling rates (10 6 ~10 7 k / s) melts metal powder to form ultrafine grains and non-equilibrium supersaturated solid solution, thus giving the printed parts excellent properties. Compared with traditional single aluminum alloys, aluminum-based composites have the advantages of high specific strength, low thermal expansion coefficient, high temperature resistance, and wear resistance, and have attracted widespread attention in the aerospace and automotive industries.

[0003] In addition, proper post-heat treatment is essential to improve the mechanical properties of L-PBF composites, especially fatigue strength. Some scholars have studied the effects of different heat treatment methods on the microstructural evolution and phase precipitation behavior of Al-Zn-Mg-Cu / TiB2 composites prepared by L-PBF. By analyzing the samples of the deposited state, direct aging, solution treatment and subsequent T6 heat treatment, it was found that the T6 sample exhibited the best performance. This is due to the formation of Al7Cu2Fe and the precipitation of η′ / η phase on TiB2 and Al7Cu2Fe. And the effect of heat treatment on the fatigue behavior of A20X composites prepared by L-PBF process. After stress relief aging, the composite material presents an ultrafine and fine equiaxed grain structure, and the yield strength, high cycle fatigue life and low cycle fatigue life are significantly improved compared with the deposited state.

[0004] Aluminum-based composite components are often subjected to fatigue loads during long-term use, which can easily cause fatigue cracks and lead to component failure. Components in long-life service are required to withstand high or even ultra-high cycles (>10 7 ) cyclic load. However, the current research on the mechanical properties of L-PBF composites mainly focuses on the evaluation of static load performance such as tension and compression, while the research on its dynamic fatigue performance is still very limited. Therefore, this patent aims to study a method for improving the fatigue performance of additively manufactured aluminum-based composites, promote the further development of aluminum-based composite additive manufacturing technology, enhance the safety and reliability of aluminum-based composite additive manufacturing components in service, reduce the occurrence of accidents and failures, and improve social benefits. Summary of the invention

[0005] The technical problem to be solved by the present invention is that the fatigue performance of existing aluminum-based composite materials is not enough to meet the needs of the industry, and a method for improving the rotational fatigue performance of additively manufactured aluminum-based composite materials is provided. The method is to perform additive manufacturing by ball milling aluminum alloy powder and TiB2 powder, and then perform heat treatment. The heat-treated additively manufactured aluminum-based composite material sample has Al6Mn phase distributed along the grain boundary, and Al3(Ti, Zr, Hf) phase exists in the fine grain area at the edge of the molten pool and the coarse grain area inside the molten pool. Due to the precipitation strengthening effect of a large amount of secondary Al6Mn and secondary Al3(Ti, Zr, Hf) phases during the heat treatment process, the heat-treated additively manufactured aluminum-based composite material sample meets the 1×10 7 The rotational fatigue load under the cycle number is greater than 175MPa.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for improving the rotational fatigue performance of additively manufactured aluminum-based composite materials, characterized in that the method comprises the following steps:

[0007] Step 1: preparing AlMnMgZrHf alloy powder by gas atomization method;

[0008] Step 2: ball-milling the AlMnMgZrHf alloy powder and TiB2 powder prepared in step 1 to obtain AlMnMgZrHf / TiB2 composite material powder;

[0009] Step 3: Additive manufacturing the composite material powder obtained in step 2 to obtain a deposited sample;

[0010] Step 4: heat-treat the deposited sample obtained in step 3 to obtain a heat-treated additively manufactured aluminum-based composite material sample.

[0011] The present invention prepares AlMnMgZrHf alloy powder by a gas atomization method to obtain AlMnMgZrHf alloy powder with uniform composition, and mixes the AlMnMgZrHf alloy powder and TiB2 powder by ball milling to fully and evenly mix the AlMnMgZrHf alloy powder and TiB2 powder, and obtains a desired deposited sample with any structure by additive manufacturing, which has a wide range of applications, and finally performs heat treatment to ensure that a large number of nano / submicron rod-shaped Al6Mn precipitated phases are formed in the aluminum-based composite material sample, and Al3 (Ti, Zr, Hf) nano-scale precipitates exist in the fine-grained area at the edge of the molten pool and the coarse-grained area inside the molten pool, thereby greatly improving the rotational fatigue performance of the aluminum-based composite material.

[0012] The above-mentioned method for improving the rotation fatigue performance of aluminum-based composite materials manufactured by additive manufacturing is characterized in that the AlMnMgZrHf alloy powder in step 1 is composed of the following components in mass percentage: Mn5.89%, Mg 2.32%, Zr0.82%, Hf 0.94%, and the balance is Al, and the average particle size of the AlMnMgZrHf alloy powder is 20μm to 60μm. The present invention reduces the powder spheroidization and agglomeration phenomena in the additive manufacturing process by controlling the forming process parameters of the AlMnMgZrHf alloy powder, and has a higher surface finish, thereby ensuring the consistency and uniformity of the additive manufacturing process and the performance of the aluminum-based composite material.

[0013] The above-mentioned method for improving the rotational fatigue performance of additively manufactured aluminum-based composite materials is characterized in that the average particle size of the TiB2 powder in step 2 is 1 μm to 3 μm. The present invention controls the average particle size of the TiB2 powder so that it can be fully mixed with the AlMnMgZrHf alloy powder, thereby ensuring the formation of the reinforcement phase in the composite material.

[0014] The above method for improving the rotational fatigue performance of additively manufactured aluminum-based composite materials is characterized in that the mass content of TiB2 powder in the composite material powder in step 2 is 2%. The present invention ensures the volume fraction of the reinforcing phase in the composite material by controlling the addition amount of TiB2 powder.

[0015] The above-mentioned method for improving the rotational fatigue performance of aluminum-based composite materials in additive manufacturing is characterized in that the process of ball milling and mixing in step 2 is: mechanically grinding at a speed of 150r / min for 4h in an omnidirectional planetary ball mill, changing the grinding direction every 20min as a cycle to prevent the ball mill from overheating, and pausing grinding for 1min every two cycles. The present invention ensures that the AlMnMgZrHf alloy powder and the TiB2 powder are fully mixed and uniform by controlling the parameters of ball milling and mixing, while preventing the ball mill from overheating.

[0016] The above-mentioned method for improving the rotation fatigue performance of aluminum-based composite materials manufactured by additive manufacturing is characterized in that the additive manufacturing process described in step three meets the following conditions: 6061 aluminum alloy is used as the substrate, and it is carried out in a vacuum chamber with an oxygen content of less than 600ppm. The composite material powder is dried at 120°C for more than 3h before forming, and the surface of the substrate is wiped with anhydrous ethanol before forming. The substrate is preheated to 150°C before forming, the laser power is 200W, the scanning speed is 1300mm / s, the layer thickness is 30μm, the track spacing is 100μm, and a chessboard scanning strategy is adopted. The scanning direction rotates 67° per layer. The present invention ensures the performance of the deposited sample by controlling the forming process parameters of additive manufacturing.

[0017] The above-mentioned method for improving the rotational fatigue performance of additively manufactured aluminum-based composite materials is characterized in that the heat treatment in step 4 is heating to 375°C and then keeping the temperature for 4 hours, and then air cooling. The present invention controls the aging heat treatment system to ensure that a large number of nano / submicron rod-shaped Al6Mn precipitation phases are formed in the aluminum-based composite material sample, and Al3 (Ti, Zr, Hf) nano-scale precipitates are precipitated in the equiaxed crystal area at the edge of the molten pool and the short columnar crystal area inside the molten pool, thereby greatly improving the rotational fatigue performance of the aluminum-based composite material sample.

[0018] The above-mentioned method for improving the rotational fatigue performance of additively manufactured aluminum-based composite materials is characterized in that the microstructure of the heat-treated additively manufactured aluminum-based composite material sample in step four shows that the grains are composed of equiaxed crystals and short columnar crystals, Al6Mn phases are distributed along the grain boundaries, and Al3(Ti, Zr, Hf) phases exist in the fine-grained zone at the edge of the molten pool and the coarse-grained zone inside the molten pool.

[0019] The above-mentioned method for improving the rotational fatigue performance of additively manufactured aluminum-based composite materials is characterized in that the hardness of the heat-treated additively manufactured aluminum-based composite material sample in step 4 is greater than 180 HV, and the hardness of the heat-treated aluminum-based composite material sample in step 4 is greater than 180 HV. 7 The rotational fatigue load under the cycle number is greater than 175MPa.

[0020] Compared with the prior art, the present invention has the following advantages:

[0021] 1. The present invention performs additive manufacturing by mixing AlMnMgZrHf alloy powder and TiB2 powder in an omnidirectional planetary ball mill to obtain a deposited sample, which is then heat treated. The microstructure of the heat-treated additively manufactured aluminum-based composite material sample is as follows: Al6Mn phase is distributed along the grain boundary, and Al3(Ti, Zr, Hf) phase exists in the equiaxed crystal zone at the edge of the molten pool and the short columnar crystal zone inside the molten pool. Due to the precipitation strengthening effect of a large amount of secondary Al6Mn and secondary Al3(Ti, Zr, Hf) phases during the heat treatment process, the aluminum-based composite material sample meets the requirements of 1×10 7 The rotational fatigue load under the cycle number is greater than 175MPa.

[0022] 2. The aluminum-based composite material sample prepared by the present invention has a multi-level heterogeneous heterogeneous structure of coarse grain area and fine grain area. Al6Mn phase is distributed along the grain boundary, and Al3(Ti, Zr, Hf) phase exists in the fine grain area at the edge of the molten pool and the coarse grain area inside the molten pool. The SN fatigue curve shows that aging heat treatment has a significant effect on the fatigue performance of the composite material. When the number of cycles reaches 1×10 7 The maximum stress level of the unheat-treated deposited sample is 140 MPa, and the maximum stress level of the heat-treated additively manufactured aluminum-based composite sample is 175 MPa.a =200MPa, the fatigue cycles of the deposited sample and the heat-treated additively manufactured aluminum matrix composite sample are Nf=8.55×10 4 and 5.7×10 6 , it can be seen that after heat treatment, the fatigue properties of additively manufactured aluminum-based composite specimens are greatly improved.

[0023] 3. The present invention prepares nearly fully dense aluminum-based composite material samples through additive manufacturing. The aluminum-based composite material samples have excellent processing properties, no solidification cracks or obvious metallurgical defects, and are suitable for preparing parts with complex structures.

[0024] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a SEM image of the composite material powder prepared in step 2 of Example 1 of the present invention.

[0026] Figure 2 This is a physical picture of the deposited sample prepared in step three of Example 1 of the present invention.

[0027] Figure 3 This is a SEM image of the aluminum-based composite material sample prepared in step 4 of Example 1 of the present invention.

[0028] Figure 4 This is the EBSD image of the aluminum-based composite material sample prepared in step 4 of Example 1 of the present invention.

[0029] Figure 5 This is an EDS image of the fine grain region of the aluminum-based composite material sample prepared in step 4 of Example 1 of the present invention.

[0030] Figure 6 This is an EDS image of the coarse grain region of the aluminum-based composite material sample prepared in step 4 of Example 1 of the present invention.

[0031] Figure 7 It is a diffraction spot pattern of the precipitation phase of the aluminum-based composite material sample prepared in step 4 of Example 1 of the present invention.

[0032] Figure 8 This is a graph showing the mechanical properties of the deposited sample prepared in step three of Example 1 of the present invention at different heat treatment temperatures.

[0033] Fig. 9 This is a graph showing the mechanical properties of the deposited sample prepared in step 3 of Example 1 of the present invention at different heat treatment times.

[0034] Fig.10It is a comparison chart of fatigue properties of the deposited sample prepared in step 3 of Example 1 of the present invention and the aluminum-based composite material sample prepared in step 4.

[0035] Fig.11 This is a macroscopic fatigue fracture diagram of the aluminum-based composite material sample prepared in step 4 of Example 1 of the present invention.

[0036] Fig.12 This is a microscopic fatigue fracture diagram of the aluminum-based composite material sample prepared in step 4 of Example 1 of the present invention. DETAILED DESCRIPTION

[0037] Example 1

[0038] This embodiment includes the following steps:

[0039] Step 1: Prepare Al-5.89Mn-2.32Mg-0.94Hf-0.82Zr alloy powder with an average particle size of 36.6 μm by gas atomization method;

[0040] Step 2: Mechanically grind the Al-5.89Mn-2.32Mg-0.94Hf-0.82Zr alloy powder prepared in step 1 with a mass ratio of 98:2 and the TiB2 powder with an average particle size of 1 μm to 3 μm in an omnidirectional planetary ball mill at a speed of 150 r / min for 4 hours, change the grinding direction every 20 minutes as a cycle, and pause the grinding for 1 minute every two cycles to obtain Al-5.89Mn-2.32Mg-0.94Hf-0.82Zr / TiB2 composite material powder;

[0041] Step 3: Magic software is used to model and slice the deposited sample. The composite material powder obtained in step 2 is additively manufactured using the BLT-S210 equipment of Platinum. The equipment adopts a dual laser configuration, and the fiber laser wavelength is 1070nm, the laser spot diameter is 80μm, and 6061 aluminum alloy is used as the substrate. The process is carried out in a vacuum chamber with an oxygen content of less than 600ppm. The composite material powder is dried at 120°C for more than 3h before forming. The surface of the substrate is wiped with anhydrous ethanol before forming. The substrate is preheated at 150°C before forming. The laser power is 200W, the scanning speed is 1300mm / s, the layer thickness is 30μm, the track spacing is 100μm, and a chessboard scanning strategy is adopted. The scanning direction is rotated 67° per layer to obtain a deposited sample.

[0042] Step 4: Heat the deposited sample obtained in step 3 to 375° C., keep it warm for 4 hours, and then air-cool it to obtain a heat-treated additively manufactured aluminum-based composite material sample.

[0043] After testing, the grains in the aluminum-based composite material sample prepared in this embodiment are composed of equiaxed crystals and short columnar crystals, Al6Mn phases are distributed along the grain boundaries, and Al3(Ti, Zr, Hf) phases exist in the equiaxed crystal region at the edge of the molten pool and the short columnar crystal region inside the molten pool; the hardness of the aluminum-based composite material sample is greater than 180HV, and the hardness is greater than 1×10 7 The rotational fatigue load under the cycle number is greater than 175MPa.

[0044] Figure 1 is a SEM image of the composite material powder prepared in step 2 of this embodiment. Figure 1 It can be seen that the TiB2 particles in the composite material powder are more evenly distributed in the alloy powder, the larger TiB2 are distributed between the powders, while the smaller ones are embedded in the matrix powder.

[0045] Figure 2 is a physical picture of the deposited sample prepared in step 3 of this embodiment. Figure 2 It can be seen that the surface of the deposited sample is relatively flat, without large cracks or other metallurgical defects, and parts of various shapes can be prepared. After testing, the density of the deposited sample prepared in this embodiment is greater than 99.8%.

[0046] Figure 3 : is a SEM image of the heat-treated additively manufactured aluminum-based composite material sample prepared in step 4 of this embodiment, which is obtained by preparing the heat-treated additively manufactured aluminum-based composite material into a SEM sample using a standard metallographic sample preparation method and testing it. Figure 3 FG represents the fine grain region, CG represents the coarse grain region, Figure 3 It can be seen that there are many submicron white block precipitates distributed at the grain boundaries of the aluminum-based composite material samples, and the white block precipitate phase (Al6Mn) at the molten pool boundary (white dotted line in the figure) is significantly increased, as well as some blocky nano-scale precipitates Al3 (Ti, Zr, Hf). This is caused by the large difference in cooling rate between the inside of the molten pool and the molten pool boundary. In addition, irregular TiB2 particles can be seen in the aluminum-based composite material samples. EDS energy spectrum analysis can prove that they are added TiB2 particles. TiB2 is distributed at the molten pool boundary and inside the molten pool in the α-Al matrix, with a size of about 1μm to 3μm, and no obvious agglomeration phenomenon is found. This is mainly due to the fact that the added TiB2 particles are larger in size on the one hand, and the added particle content is relatively small on the other hand.

[0047] Figure 4 is the EBSD image of the heat-treated additively manufactured aluminum-based composite material sample prepared in step 4 of this embodiment, Figure 4 FG represents the fine grain region, CG represents the coarse grain region, Figure 4It can be seen that there are mainly fine grains at the edge of the molten pool of the aluminum-based composite sample, and there are coarse grain areas inside the molten pool. This is due to the heterogeneous nucleation effect caused by TiB2 particles and nano-scale precipitates. <100> There is texture orientation in the direction, the MUD (multiple uniform density) value is 1.9, and the grain size is calculated based on the equivalent circular diameter of the grain. According to statistics, the average grain size is 1.57±0.79μm, and the area with grain size less than 1μm accounts for 24.2%.

[0048] Figure 5 is an EDS image of the fine grain region of the heat-treated additively manufactured aluminum-based composite material sample prepared in step 4 of this embodiment, Figure 6 This is the EDS image of the coarse grain area of ​​the heat-treated additively manufactured aluminum-based composite material sample prepared in step 4 of this embodiment. Figure 5 and Figure 6 It can be seen that the prepared aluminum-based composite material sample contains Mn-rich phase as well as Ti-, Zr-, and Hf-rich phases, and the distribution of each element is uniform.

[0049] Figure 7 This is the diffraction spot diagram of the precipitation phase of the heat-treated additively manufactured aluminum-based composite material sample prepared in step 4 of this embodiment. After analysis, the left image is Al3 (Ti, Zr, Hf) phase, and the right image is Al6Mn phase. Figure 7 It can be seen that the Al3(Ti, Zr, Hf) phase and Al6Mn phase present in the sample are due to the extremely high cooling rate during the rapid solidification process, which causes a large number of solute atoms to exist in the form of supersaturated solid solution. The solubility of solute atoms decreases during heat treatment, resulting in a large amount of precipitation of the second phase from the matrix.

[0050] The deposited samples prepared in step 3 of this embodiment were heat treated at 275°C, 300°C, 325°C, 350°C, 375°C, 400°C, 425°C, 450°C, and 475°C for 4 hours, and then hardness tests were performed to obtain Figure 8 , Figure 8 The middle dashed line represents the hardness of the conventional heat treatment, that is, heating at 500℃ for 2h and then heating at 180℃ for 10h. The final hardness of the material is 130HV. Figure 8 It can be seen that the hardness of the deposited sample after heat treatment shows a trend of first increasing and then decreasing with the heat treatment temperature, corresponding to the under-aging, peak aging and over-aging stages, and reaches a maximum of 180±2HV at 375℃.

[0051] The deposited sample prepared in step 3 of this embodiment was heat treated at 375°C for 0 h, 1 h, 2 h, 4 h, 8 h, and 16 h, and then hardness tested to obtain Fig. 9 , Fig. 9The middle dashed line represents the hardness of the conventional heat treatment, that is, heating at 500℃ for 2h and then heating at 180℃ for 10h. The final hardness of the material is 130HV. Fig. 9 It can be seen that the hardness of the deposited sample after heat treatment shows a trend of first increasing and then decreasing with the heat treatment time, and reaches a maximum of 180HV after heat treatment for 4h.

[0052] Combination Figure 8 and Fig. 9 The optimal heat treatment solution was found to be 375℃ for 4h and cooling in air.

[0053] The deposited sample prepared in step 3 of this embodiment and the heat-treated aluminum-based composite material sample prepared in step 4 were subjected to surface grinding and polishing treatments to reduce the potential influence of surface roughness on fatigue performance. Then, a room temperature rotation fatigue test was carried out using a CARLCSHENCKAG fatigue testing machine. The loading frequency was 60 Hz, the stress ratio was -1, and the waveform was a sine wave. Each sample was loaded until it was completely broken or until the cycle count reached 1×10 7 , the results are shown in Fig.10 , Fig.10 The arrowed curves are the SN (fatigue life-loading load) curves of the deposited sample (above) and the heat-treated aluminum matrix composite material (below). Fig.10 It can be seen that heat treatment has a significant effect on the fatigue properties of the material. When the number of cycles reaches 1×10 7 The maximum stress level of the unheat-treated deposited sample is 140MPa, and the maximum stress level of the heat-treated aluminum matrix composite sample is 175MPa. a =200MPa, the fatigue cycles of the deposited sample and the heat-treated aluminum matrix composite sample are N f =8.55×10 4 and 5.7×10 6 , indicating that after heat treatment, the fatigue properties of the aluminum-based composite material specimens are significantly improved. The improvement in fatigue properties can be attributed to the precipitation strengthening effect of a large amount of secondary Al6Mn and secondary Al3(Ti,Zr,Hf) phases during the heat treatment process. In addition, the fatigue life of the fatigue performance curve in the low-cycle fatigue region varies greatly, while the fatigue life in the high-cycle fatigue region tends to converge.

[0054] Fig.11 is a macroscopic fatigue fracture diagram of the heat-treated aluminum-based composite material sample prepared in step 4 of this embodiment, Fig.12 is a microscopic fatigue fracture diagram of the heat-treated aluminum-based composite material sample prepared in step 4 of this embodiment, Fig.11The circle in the upper left corner indicates the fracture source, the dotted line indicates the crack propagation direction, and the other circles indicate tiny defects. Fig.11 and Fig.12 It can be seen that fatigue cracks are mainly initiated by pores and poor fusion defects near the surface of the specimen, and then radially extend into the material. Fig.11 Three different stages of typical fatigue fracture of composite materials were revealed: fatigue crack initiation stage, steady-state crack extension stage and final instantaneous fracture stage. In addition, the fracture surface showed an uneven distribution of multi-scale grains both inside and at the boundary of the molten pool. The boundary of the molten pool was mainly composed of fine grains, while the interior was composed of larger coarse grains.

[0055] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for improving the rotational fatigue performance of additively manufactured aluminum-based composite materials, characterized in that: The method comprises the following steps: Step 1: preparing AlMnMgZrHf alloy powder by gas atomization method; Step 2: ball-milling the AlMnMgZrHf alloy powder and TiB2 powder prepared in step 1 to obtain AlMnMgZrHf / TiB2 composite material powder; Step 3: Additive manufacturing the composite material powder obtained in step 2 to obtain a deposited sample; Step 4: heat-treat the deposited sample obtained in step 3 to obtain a heat-treated additively manufactured aluminum-based composite material sample.

2. A method for improving the rotational fatigue performance of additively manufactured aluminum-based composite materials according to claim 1, characterized in that: The AlMnMgZrHf alloy powder in step 1 is composed of the following components in mass percentage: Composition: Mn 5.89%, Mg 2.32%, Zr 0.82%, Hf 0.94%, and the balance is Al. The average particle size of the AlMnMgZrHf alloy powder is 20 μm to 60 μm.

3. The method for improving the rotational fatigue performance of additively manufactured aluminum-based composite materials according to claim 1, characterized in that: The average particle size of the TiB2 powder in step 2 is 1 μm to 3 μm.

4. A method for improving the rotational fatigue performance of additively manufactured aluminum-based composite materials according to claim 1, characterized in that: The mass content of TiB2 powder in the composite material powder in step 2 is 2%.

5. The method for improving the rotational fatigue performance of additively manufactured aluminum-based composite materials according to claim 1, characterized in that: The ball milling mixing process in step 2 is: mechanically grinding at a speed of 150 r / min for 4 hours in an omnidirectional planetary ball mill, changing the grinding direction every 20 minutes as a cycle, and pausing the grinding for 1 minute every two cycles.

6. The method for improving the rotational fatigue performance of additively manufactured aluminum-based composite materials according to claim 1, characterized in that: The additive manufacturing described in step three meets the following conditions: 6061 aluminum alloy is used as the substrate, the surface of the substrate is wiped with anhydrous ethanol before forming, the composite material powder is dried at 120°C for more than 3 hours before forming, and is carried out in a vacuum chamber with an oxygen content of less than 600 ppm. The substrate is preheated to 150°C before forming, the laser power is 200 W, the scanning speed is 1300 mm / s, the layer thickness is 30 μm, the track spacing is 100 μm, a chessboard scanning strategy is adopted, and the scanning direction is rotated 67° per layer.

7. The method for improving the rotational fatigue performance of additively manufactured aluminum-based composite materials according to claim 1, characterized in that: The heat treatment in step 4 is heating to 375°C, keeping the temperature for 4 hours, and air cooling.

8. The method for improving the rotational fatigue performance of additively manufactured aluminum-based composite materials according to claim 1, characterized in that: The microstructure of the heat-treated additively manufactured aluminum-based composite material sample described in step 4 is characterized by grains composed of equiaxed crystals and short columnar crystals, Al6Mn phases distributed along the grain boundaries, and Al3(Ti, Zr, Hf) phases in the fine-grained area at the edge of the molten pool and the coarse-grained area inside the molten pool.

9. The method for improving the rotational fatigue performance of additively manufactured aluminum-based composite materials according to claim 1, characterized in that: The hardness of the heat-treated additively manufactured aluminum-based composite material sample in step 4 is greater than 180 HV. 7 The rotational fatigue load under the cycle number is greater than 175MPa.